Research in organizational change and development. Volume 26 - Noumair, Debra A.; Shani, Abraham B. (Emerald Publishing Limited, 2018)
This volume providesnew conceptual insights, robust empirical studies, and thought-provoking chapters to help organizations improve health and wellbeing insociety. Some chapters dothis by addressing macro-level change: for example, consulting at the eco-system level anddiscussing the challenges entailed in developing intervention capabilities toimpact highly interdependent eco-systems; or discussing the learning and experience of a large system transformation projectconducted at a national level that had an impact on societal health andwellbeing. Other chapters extendtheory and integrate perspectives that heretofore have remained separate, suchas the 2017 Pasmore-Woodman Award winners, who provide an overview of theircollaborative attempts at intervening and making a difference in organization studies. The richness of the diverse collaborative contributions to thisvolume by leading scholars and scholar-practitioners from around the globeprovide an enriching and emerging body of knowledge.
Prelims -- Working toward sustainable development: consulting to the eco-system -- Enhancing 360-degree feedback for individual assessment and organization development: methods and lessons from the field -- Organization renewal through entrepreneurial initiatives: when the seed changes the soil -- A test of the theory of planned behavior: influencing behavioral change to go "green" -- The colors of change revisited: situating and describing the theory and its practical applications -- Organizing intelligence (oq): the source of productive workplaces -- Champions of change and organizational development: a return to schön and typology for future research and practice -- Agents of change: insights from three case studies of hospital transformations -- System change at national government level -- Opening spaces and living in the limits: attempts at intervening in organization studies -- About the authors.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Organizational change; Social responsibility of business; Business & Economics -- Organizational Behavior; Organizational theory & behaviour